The Influence of Work-Life Balance and Job Satisfaction on the Performance of Millennial and Gen Z Employees with Employee Engagement as an Intervening Variable - Armahfia Amami; M. Ridwan Basalamah; Abdullah Syakur Novianto (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Shifts in the workforce's demographic structure have led to workplaces being increasingly dominated by Millennials and Generation Z, presenting new challenges for human resource management—particularly regarding differences in characteristics, communication styles, work ethics, and expectations for work-life balance, all of which can trigger interpersonal conflict and impact productivity. This study aims to analyze and explain the influence of work-life balance (WLB) and job satisfaction on employee performance, with employee engagement serving as an intervening variable, among Millennial and Generation Z employees at PT Jhonlin Agro Raya Tbk in Batulicin, South Kalimantan. A quantitative approach utilizing explanatory research methods was employed. Data collection was conducted through the distribution of questionnaires both in person and via Google Forms using a 1-5 Likert scale. Non-probability sampling was used via a saturated sampling approach, resulting in a total of 291 respondents: 186 Millennials (63.9%) and 105 Generation Z employees (36.1%). The respondent demographic was predominantly male (66.7%), with the majority having a tenure of 1-3 years (49.8%). Data analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software, alongside a Multi-Group Analysis (MGA) approach to compare the generational groups. Evaluation of the measurement model (outer model) revealed that all variable indicators had loading factor values ​​> 0.6 and Average Variance Extracted (AVE) values ​​> 0.5, thereby meeting convergent and discriminant validity requirements the model also demonstrated reliability, with composite reliability values ​​> 0.7. Evaluation of the structural model (inner model) indicated good predictive relevance (Q2 > 0) and a high level of overall model fit (high Goodness of Fit Index: 0.512 for Millennials and 0.657 for Gen Z). The R-squared values ​​for the Millennial generation group indicate that 43.7% of the variation in employee performance (a moderate level) and 50.9% of the variation in employee engagement can be explained by the model. Meanwhile, for the Generation Z group, the model strongly explains 69.3% of the variation in employee performance and 60.8% of the variation in employee engagement. Overall, work-life balance and job satisfaction were found to have a positive impact on both employee engagement and employee performance, with employee engagement serving as an effective mediator bridging this relationship across both workforce generations at PT Jhonlin Agro Raya Tbk.